Medición del impacto financiero en la reestructuración administrativa, operativa y financiera de la fábrica de calzado vicalza - Sigüenza, E. (2009)
The present project shows the mensuration of the financial impact starting from the administrative, operative and financial restructuring of the factory of footwear Vicalza; which is devoted to the production and footwear commercialization in leather in Ecuador. The factory in study presents inconveniences in different areas, for that has shown evidences of declines in the evolution that which has prevented it to grow to a high rhythm inside the market, for this reason it seeks to be carried out correctives in this areas to obtain a good yield starting from the improvement in the organization of the activities and the establishment of a structural appropriate organization that it allows to improve the conditions of this factory. The restructuring proposes the analysis and the implementation of strategies, mechanisms and procedures in all the areas of the factory; later on the financial impact will be observed that would have the restructuring proposed for the improvement of the factory, obtaining benefits for the appropriate planning, organization, management and control of resources, allowing it to achieve a bigger growth in the utility and avoiding setbacks in the production processes and delivery.